Social environment affects beak color in captive male House Sparrows "Passer domesticus" - Lombardo, Michael P.; Thorpe, Patrick A.; Colpetzer, Sheila (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Black beak color in male House Sparrows ("Passer domesticus") is a secondary sexual characteristic whose expression is directly correlated with testosterone levels. To experimentally determine if social environment affects black beak color and by implication testosterone levels, we housed wild-caught male sparrows either individually (n = 10), "Solo" males, or in the company of two other males (n = 4 "Group"s of 3 males), "Group" males, from 26 May - 7 July 2006.
Keywords: captivity; House Sparrows; Passer domesticus; testosterone